Implikasi Kearifan Lokal terhadap Loyalitas Konsumen dalam Pembelian Kain Tenun Melayu Riau - Rosmayani Rosmayani; Annisa Mardatillah (Universitas Riau, 2023)
This study purpose to examine in depth about consumer loyalty as an implication of lokal wisdom through consumer trust of Riau Malay woven fabric buyers. This research was conducted descriptively and verifiably with a survey method on 100 buyers of Riau Malay woven fabric. The analytical tool used is SEM-PLS. The results showed that consumers of Riau Malay woven fabric related to lokal wisdom believe that each pattern and color on the fabric contains noble values of Malay culture, consumer confidence in Riau Malay woven fabric is also still good and consumers remain loyal and continue to make repeat purchases of the woven fabric. the results also show that lokal wisdom affects consumer loyalty through consumer confidence in accordance with the model built.